The Correlation of Wealth between Parents and Children in Australia - Peter Siminski; Sin Hung Yu (Institute of Labor Economics (IZA), 2021)
We present the first estimates of intergenerational wealth correlation for Australia, using HILDA. The rank correlation varies greatly by child age when wealth is observed, from 0.1 before age 30, to 0.5 after age 40. Most children in our estimation sample are young. For these children overall, the estimate is 0.253. Our comparable estimate for the USA is 0.306. Wealth correlations are difficult to interpret and not well grounded in theory. We therefore also implement Boserup et al.'s (2017) framework to estimate the intergenerational correlation of lifetime resources, but conclude that HILDA is not yet mature enough for this task.
Keywords: D31; J62; H00; 330; intergenerational mobility; wealth mobility; Australia